Use of Infection Prevention Bundle for Cesarean Section to Control Post-Surgical Infections: A Causal-Comparative Study - Rakhshanda Toheed, Sarma Shehzadi, Maimoona Attaria (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To compare the effectiveness of the infection prevention bundle approach with the traditional injectable and oral prolonged antibiotic method to control cesarean section surgical site infection (CS-SSI) in a predominantly unbooked and low-income population. Methods: A prospective causal comparative study in a tertiary care hospital. One hundred and eighty-four pregnant women planned for cesarean sections, with no recent infection, were chosen by simple random sampling method and divided into two groups. Group A patients (92) were managed by an infection prevention bundle that consisted of pre-operative bathing, a single dose of injectable cephalexin (1-2 grams) intravenously within one hour of incision, and spontaneous removal of the placenta. Group C patients (92) were managed by the traditional method, which is injection of ceftriaxone (1-2 grams) intravenously for 48 hours, followed by oral antibiotics for 5 days. Results:The infection rate in group A was 2.2% versus 1.1% in group C patients, with no statistically significant difference between the two groups (pp value: 0.259). A significant difference is observed in pre-op Hb levels (p-value = 0.003), with <9 gm/dl being 4 (4.3%) in Group A and 9 (9.8%) in Group C, 9-11 gm/dl being 69 (75%) in Group A and 47 (51.1%) in Group C, and >11 gm/dl being 19 (20.7%) in Group A and 36 (39.1%) in Group C. Pre-operative total leucocyte count, anesthesia type, duration of C-section, complications, and blood loss show no significant differences between the groups. Conclusion: The infection prevention bundle approach is simple, cheap, applicable, and effective in controlling cesarean section surgical site infection in low income populations. Keywords: infection prevention bundle, infection rate,Cesarean Section, Post-Surgical Infections